Application of Project-Based Learning Learning Model Assisted by Geogebra Application to Improve Students' Mathematical Reasoning Ability at MTS Nurul Islam Indonesia Medan - Ilmi Fadila Harahap; Sri Lestari Manurung (Asian Journal of Applied Education (AJAE), 2023)
The purpose of this study was to determine the improvement of students' mathematical reasoning abilities by applying the Geogebra-assisted Project Based Learning learning model in class VIII-1 MTs Nurul Islam Indonesia Medan in the 2022/2023 academic year. The subjects in this study were students of class VIII-1 MTs Nurul Islam Indonesia Medan, amounting to 20 people. The data collection techniques used were teacher observation sheets, tests of mathematical reasoning abilities and documentation. This research is a classroom action research (CAR) which consists of 2 cycles, each cycle consists of 2 meetings. Before taking the action, an initial test is given and at the end of each cycle a student's mathematical reasoning ability test is given. The results of the students' mathematical problem reasoning ability test increased from the initial test, cycle I, and cycle II. In the classical initial test, 4 students (20%) completed and the average initial test ability was 56.29 with a very low level of ability category. In the classical first cycle test, 4 students (20%) completed and the average ability test was 57.22 with a very low level of ability category. Then in the second cycle test, classically, 17 students (85%) completed and the average ability was 89.44 with a high level of ability. Thus, it can be concluded that the application of the project based learning model assisted by the geogebra application to improve students' mathematical reasoning abilities at MTs Nurul Islam Indonesia Medan.